PENGARUH KONSUMSI JAJANAN TERHADAP KESEHATAN GIGI DAN MULUT ANAK SEKOLAH DASAR DI KOTA BANJARBARU - Waljuni Astu Rahman (Poltekkes Kemenkes Banjarmasin, 2021)
The 2018 Basic Health Research shows that nationally the DMF-T index of dental caries has the highest prevalence in South Kalimantan where the population aged 12 years and over is 49.5% experiencing caries in their teeth that have not been treated/active caries in women is higher than men. men, and in urban areas it is higher than in rural areas. Whereas for the city of Banjarbaru, based on the 2021 report, the dental caries rate reached 58.5%. The purpose of this study was to determine the effect of snack consumption on the dental and oral health of elementary school children in the Banjarbaru City Region. The type of research used was analytic survey research with a cross-sectional approach, taking samples using purposive sampling, namely children in grades IV, V and VI from 6 elementary schools in Banjarbaru totaling 460 students. Analysis of the data used to analyze the research variables used correlation analysis The results showed that the percentage of pocket money for sweet snacks per day used by elementary school children in Banjarbaru City was on average 51.6% of the money given by parents was used to buy sweet snacks. The dental caries rate in elementary schools in Banjarbaru City was 2.62 which showed an average of 2.62 cavities per child for each child suffering from dental caries. The dental and oral hygiene score in elementary schools in Banjarbaru City is 2.03 which shows that the average dental and oral hygiene condition for each child is in the moderate category. The conclusion of the study shows that there is an effect of consumption of sweet snacks on dental caries and oral hygiene in elementary school children in Banjarbaru City.